Circumscribed astrocytic gliomas: Contribution of molecular analyses to histopathology diagnosis in the WHO CNS5 classification - Yazgı Köy; Tarik Tihan (Wolters Kluwer Medknow Publications, 2022)
The newest revision of the WHO classification of tumors of the central nervous system, also known as WHO 5th edition, introduces substantial changes, especially within the glial tumor category and separates adult-type and pediatric-type glial tumors into different categories for the first time. In addition, another category of glial tumors, "Circumscribed Astrocytic Gliomas" were also created. This group includes pilocytic astrocytoma, pleomorphic xanthoastrocytoma, subependymal giant cell astrocytoma, chordoid glioma, astroblastoma, and the highly nebulous novel entity high-grade astrocytoma with piloid features. We present a brief and critical review of the pathological and molecular characteristics of these often well-demarcated tumors that can occur in adults as well as in the pediatric population.